Novel Totto-Chan by Tetsuko Kuroyanagi: A Study of Philosophy of Progressivism and Humanism and Relevance to the Merdeka Curriculum in Indonesia - Amaruddin Hidar; Dardiri Achmad; Efianingrum Ariefa; Hung Ruyu; Purwanta Edi (De Gruyter, 2024)
This research analyzes the educational philosophy of progressivism and humanism in Tetsuko Kuroyanagi's Totto-Chan Novel and its relevance to the Independent Curriculum in Indonesia. This study uses qualitative content analysis to reveal the progressive and humanistic educational philosophy in Totto-Chan and its relevance to the Merdeka Curriculum in Indonesia. The research involves reading the novel, extracting relevant texts, categorizing them by topics, and analyzing the relationship between these philosophies and the curriculum then the findings, detailed in a comprehensive manner, highlight indicators of progressive and humanistic educational philosophies. This research aims to identify parallels between the Merdeka Curriculum and progressivism and humanism in the Totto-Chan novel to assess the suitability and potential integration of educational philosophies. The result showed that Tetsuko Kuroyanagi's Totto-Chan novel intensely reveals the progressive and humanistic educational philosophy at Tomoe Gakuen. The school prioritizes independent learning goals, equality, justice, self-reflection, environmental connection, and shared decision-making. Principal Mr. Kobayashi educate students' independence based on interests and talents. This aligns with the Merdeka Curriculum in Indonesia, which emphasized meaningful learning design for students' independence, equality, self-reflection, environmental connection, and democratic learning principles through the concept of Merdeka Belajar in the learning process. This implication can serve as a practical learning idea for educators, fostering harmony in educational philosophy and enhancing the implementation of the recently introduced Merdeka Curriculum in Indonesia.